The effect of the subthreshold oscillation induced by the neurons' resonance upon the electrical stimulation-dependent instability - Yu, Shoujun; Yue, Wenji; Guo, Tianruo; Liu, Yonghong; Zhang, Yapeng; Khademi, Sara; Zhou, Tian; Xu, Zhen; Song, Bing; Wu, Tianzhun; Liu, Fenglin; Tai, Yanlong; et al. (Frontiers in Neuroscience, 2023)
Repetitive electrical nerve stimulation can induce a long-lasting perturbation of the axon's membrane potential, resulting in unstable stimulus-response relationships. Despite being observed in electrophysiology, the precise mechanism underlying electrical stimulation-dependent (ES-dependent) instability is still an open question. This study proposes a model to reveal a facet of this problem: how threshold fluctuation affects electrical nerve stimulations. This study proposes a new method based on a Circuit-Probability theory (C-P theory) to reveal the interlinkages between the subthreshold oscillation induced by neurons' resonance and ES-dependent instability of neural response. Supported by in-vivo studies, this new model predicts several key characteristics of ES-dependent instability and proposes a stimulation method to minimize the instability. This model provides a powerful tool to improve our understanding of the interaction between the external electric field and the complexity of the biophysical characteristics of axons.